THE DIFFERENCE OF NUMBERED HEADS TOGETHER AND COMMUNITY LANGUAGE LEARNING METHOD ON THE STUDENTS’ ABILITY TO BUILD UP DIRECT AND INDIRECT SPEECH - Sholihatul Hamidah Daulay (VISION, 2017)
Language is a set of rules used by human as a tool of their communication. The use of the language is governed by the conventional rules. Otherwise, they cannot use it effectively for the sake of their communication. They cannot communicate well. Even worst, they cannot understand each other. Therefore, in order to be successful to join a communicative interaction, the members of a speech community must use their language according to the conventional rules they share among themselves1. English as an international language plays important role in every side of the world. Therefore, we have to competent in English to get the achievement in the world competition that needed a loyal.